Rancang Bangun Sistem Otomatisasi Pergantian Air Kolam Budidaya Ikan Nila Berdasarkan Parameter Kondisi Air Menggunakan Nodemcu ESP8266 - Cintya Nada Anjali; Moch Lutfi (Faculty of Computer Science, University of Jember, 2023)
Water quality in ponds is a physical factor that influences tilapia cultivation. In general, tilapia can grow at a degree of acidity (pH) 5-9 with a maximum air turbidity of 50NTU. Cases of tilapia death in GIP Housing Martopuro Village often occur due to a lack of attention in maintaining the quality of pond water. So with the case study method that aims to solve these problems a system is designed that can monitor water quality and automatic water changes based on water condition parameters through the